PERSEPSI PELAKU PROGRAM CORPORATE SOCIAL RESPONSIBILITY DI PERUSAHAAN DARI PERSPEKTIF KETERPAKASAAN - Affandy, Doddy (Fakultas Ekonomi Universitas Wisnuwardhana, 2021)
Abstract:The purpose of this study is to determine the implementation of CSR in the company and interpret CSR as an obligation to the company as a result of the company law number 40 of 2007 regarding CSR obligations so that the true meaning in carrying out this CSR will be known. This study uses a qualitative method with a phenomenological approach using interpretive paradigms in explaining phenomena that occur. The results showed that the CSR program practitioners in the company considered that the CSR program established by the company had run well and was beneficial to both parties. Perceptions of corporate CSR program actors are significantly related to the level of implementation of CSR programs, and CSR is used as a way of life within thecompany. Keywords: corporate social responsibility practices, Undang-undang No. 40 of 2007, corporate culture.